(3GdehGYX GdHGdZIs - (3GdgeOGfj, GdcGXej, eMeO Hf YHO GdhgGH Hf OGhO, J (B1303(3g`s ((3eMeO Hf GdMSjf fLa CHGOjs)
(3ChdgG (B:s
(3GdMeO ddg Pj Gdeff hGdBdGA GdSGHZI(B... (3CeG HYO(B... (3Ef GdehGYX CYXe eG jLdh UOC GdbdhH hCLd eG jUbd Yf GdCaFOI ZHGQ GdeYGUj(B...s
(3BNQgG (B:s
(3cdeG PcQ CKQ GdMRf hGdCSbGe aj bdhH GdCfGe(B. (3GdefRd GdKGdK YTQ (B... (3hdjcf gPG BNQ eG fedjg(B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs